Limits of ultra: towards an interdisciplinary understanding of ultra-endurance running performance - Berger, N. J. A.; Best, R.; Best, A. W.; Lane, A. M.; Millet, G. Y.; Barwood, M.; Marcora, S.; Wilson, P.; Bearden, S. (Sports Medicine, 2024)
Ultra-endurance running (UER) poses extreme mental and physical challenges that present many barriers to completion, let alone performance. Despite these challenges, participation in UER events continues to increase. With the relative paucity of research into UER training and racing compared with traditional endurance running distance (e.g., marathon), it follows that there are sizable improvements still to be made in UER if the limitations of the sport are sufficiently understood. The purpose of this review is to summarise our current understanding of the major limitations in UER. We begin with an evolutionary perspective that provides the critical background for understanding how our capacities, abilities and limitations have come to be. Although we show that humans display evolutionary adaptations that may bestow an advantage for covering large distances on a daily basis, these often far exceed the levels of our ancestors, which exposes relative limitations. From that framework, we explore the physiological and psychological systems required for running UER events. In each system, the factors that limit performance are highlighted and some guidance for practitioners and future research are shared. Examined systems include thermoregulation, oxygen delivery and utilisation, running economy and biomechanics, fatigue, the digestive system, nutritional and psychological strategies. We show that minimising the cost of running, damage to lower limb tissue and muscle fatigability may become crucial in UER events. Maintaining a sustainable core body temperature is critical to performance, and an even pacing strategy, strategic heat acclimation and individually calculated hydration all contribute to sustained performance. Gastrointestinal issues affect almost every UER participant and can be due to a variety of factors. We present nutritional strategies for different event lengths and types, such as personalised and evidence-based approaches for varying types of carbohydrate, protein and fat intake in fluid or solid form, and how to avoid flavour fatigue. Psychology plays a vital role in UER performance, and we highlight the need to be able to cope with complex situations, and that specific long and short-term goal setting improves performance. Fatigue in UER is multi-factorial, both physical and mental, and the perceived effort or level of fatigue have a major impact on the ability to continue at a given pace. Understanding the complex interplay of these limitations will help prepare UER competitors for the different scenarios they are likely to face. Therefore, this review takes an interdisciplinary approach to synthesising and illuminating limitations in UER performance to assist practitioners and scientists in making informed decisions in practice and applicable research.